O brand love no contexto brasileiro: um estudo da comparação de escalas de sua mensuração - Bizarrias, Flávio Santino (2014)
Brands play an important role in the marketing strategy of organizations . In an increasingly competitive environment , establishing significant differences in the perception of consumers is a daily challenge. The brands provide opportunities for intensifying relations with consumers in a more abstract and subjective level , so that it creates ties difficult be broken . At the same time , consumers find in brands na opportunity to extend their identity. Based on the theory of the relationship with a brand, the construct of Brand Love is very recent in literature, and establishes that consumers form strong emotional relationships with brands , expanding their identity. Research has been undertaken to determine ways to measure the construct , however, there is a wide range of scales , with no consensus among researchers about which is more effective in this goal. This study sought to compare three scales to measure the construct of Brand Love, and its influence on loyalty , positive word-of - mouth and utilitary perception value as dependent variables. We obtained a sample of 699 respondents , university students in the city of São Paulo. Initially an exploratory study was undertaken on the scales on half of this sample, and then an empirical application was performed for the measurement of Brand Love in the rest of the sample for confirmatory study using structural equation modeling. It was found that the scale of Carroll and Ahuvia (2006 ) obtained better results in explaining the dependent variables chosen.